Réponses

  • Utilisateur Brainly
2013-06-04T18:25:10+02:00

{a x (-2) + b = 4

{a x 1 + b = -3

 

donc par différence : -3a=7

donc a=-7/3

 

ainsi -7/3+b=-3

donc b=-3+7/3

donc b=-2/3

 

donc S={(-7/3;-2/3)}

Meilleure réponse !
2013-06-04T18:35:23+02:00

Bonjour

 

-2a +b = 4

a +b = -3

 

tu multiplies la 2ème équation par -1 pour éliminer les b. Tu as :

-2a +b = 4

-a -b = 3

 

-3a = 7 d'où a = -7/3

 

a+b = -3

-7/3 +b = -3

b = -9/3 +7/3

b = -2/3

 

vérification

a +b = -3

-7/3 -2/3 =- 3

-9/3 = -3

-3 = -3